Industrial biotechnology of vitamins, biopigments, and antioxidants - Vandamme, Erick J., 1943-; Revuelta, Jos e Luis (Wiley-VCH, 2016)
Vitamins are a group of physiologically very important, chemically quite complex organic compounds, that are essential for humans and animals. Some vitamins and other growth factors behave as antioxidants, while some can be considered as biopigments. As their chemical synthesis is laborious, their biotechnology-based synthesis and production via microbial fermentation has gained substantial interest within the last decades. Recent progress in microbial genetics and in metabolic engineering and implementation of innovative bioprocess technology has led to a biotechnology-based industrial production of many vitamins and related compounds. Divided into three sections, this volume covers: 1. water-soluble vitamins 2. fat-soluble vitamin compounds and 3. other growth factors, biopigments, and antioxidants. They are all reviewed systematically: from natural occurrence and assays, via biosynthesis, strain development, to industrially-employed biotechnological syntheses and applications.